Challenges and Issues in Spatial Data Infrastructure (SDI) Development in Iraq - Al-Bakri, Maythm; Fairbairn, David (Geomatics and Environmental Engineering, 2023)
This paper addresses the nature of Spatial Data Infrastructure (SDI), considered as one of the most important concepts to ensure effective functioning in a modern society. It comprises a set of continually developing methods and procedures providing the geospatial base supporting a country’s governmental, environmental, economic, and social activities. In general, the SDI framework consists of the integration of various elements including standards, policies, networks, data, and end users and application areas. The transformation of previously paper-based map data into a digital format, the emergence of GIS, and the Internet and a host of online applications (e.g., environmental impact analysis, navigation, applications of VGI data, governmental efficiency drives) have led to huge leaps forward in SDI development. However, SDI progress can be held back by numerous challenges, both technical and non-technical. The paper outlines these challenges from the perspective of the country of Iraq, where there is an absence of a clear direction towards efficient SDI operation and a lack of knowledge for establishing and managing effective SDI. These challenges could be met by considering and resolving generic issues, identified by the experiences of other nations, by researchers, and by organisations. These issues are investigated and assessed by means of a questionnaire survey and interviews, directed towards important participants in the field of SDI development in the country. The results present the SDI issues in order of relevance to assist developers and users in solving potential SDI and data integration problems within Iraq.